The role of cerebral ischemia clinical forms in surgical treatment of patients with ruptured arterial aneurysms complicated by angiospasm - Tsimeyko, O. A.; Moroz, V. V.; Skorokhoda, I. I. (Ukrainian Neurosurgical Journal)
We revealed data analyses of examination and surgical treatment of 256 patients with vasospasm after cerebral arterial aneurysm rupture that were operated in clinic during 2000–2002. We classify 3 forms of ischemia that define different methods of surgical treatment, based on clinical, neurological, instrumental examination.